Simulation of Storm Runoff Under Different Recurrence Periods in Jinfeng District of Yinchuan - HOU Jingwei; SUN Shiqin (Renmin Zhujiang)
Visual simulation of urban storm runoff can reveal the spatiotemporal laws of urban catchment runoff,node overflow,pipe network drainage,and waterlogging risk under different recurrence periods.This research selected the central part of the Jinfeng District in Yinchuan,China,as the study area.Runoff in each sub-catchment,drainage capacity of the pipe network,and the urban waterlogging risk under different recurrence periods were simulated through the stormwater management model (SWMM) and the geographic information system (GIS).The results show that the total rainfall,surface water storage,surface runoff,and runoff coefficient all increase with the recurrence period.There are positive correlations of rainfall intensity with the depth,time,and area of node waterlogging,area of the high waterlogging risk region,and the maximum depth and time of full flow in pipes.Node overflow mainly occurs in low-lying areas and regions with large catchments,dense populations,or large impervious areas.GIS and SWMM can be used to visually simulate the urban storm runoff and assess the drainage capacity of the pipe network and the urban waterlogging risk under different recurrence periods.The results of this research can provide a reference for the maintenance of urban pipe networks,the prevention and control of waterlogging disasters,and the construction of sponge cities.